Coffee consumption and gastric cancer: a pooled analysis from the Stomach cancer Pooling Project consortium. Issue 2 (17th September 2021) - Martimianaki, Georgia; Bertuccio, Paola; Alicandro, Gianfranco; Pelucchi, Claudio; Bravi, Francesca; Carioli, Greta; Bonzi, Rossella; Rabkin, Charles S.; Liao, Linda M.; Sinha, Rashmi; Johnson, Ken; Hu, Jinfu; et al.
Abstract : Objective: This study aimed to evaluate and quantify the relationship between coffee and gastric cancer using a uniquely large dataset from an international consortium of observational studies on gastric cancer, including data from 18 studies, for a total of 8198 cases and 21 419 controls. Methods: A two-stage approach was used to obtain the pooled odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) for coffee drinkers versus never or rare drinkers. A one-stage logistic mixed-effects model with a random intercept for each study was used to estimate the dose–response relationship. Estimates were adjusted for sex, age and the main recognized risk factors for gastric cancer. Results: Compared to never or rare coffee drinkers, the estimated pooled OR for coffee drinkers was 1.03 (95% CI, 0.94–1.13). When the amount of coffee intake was considered, the pooled ORs were 0.91 (95% CI, 0.81–1.03) for drinkers of 1–2 cups per day, 0.95 (95% CI, 0.82–1.10) for 3–4 cups, and 0.95 (95% CI, 0.79–1.15) for five or more cups. An OR of 1.20 (95% CI, 0.91–1.58) was found for heavy coffee drinkers (seven or more cups of caffeinated coffee per day). A positive association emerged for high coffee intake (five or more cups per day) for gastric cardia cancer only. Conclusions: These findings better quantify the previously available evidence of the absence of a relevant association between coffee consumption and gastric cancer.